BAHASA ARAB SEBAGAI BAHASA KEDUA (KAJIAN TEORETIS PEMEROLEHAN BAHASA ARAB PADA SISWA NON-NATIVE) - Ahmad Habibi Syahid (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
Discussing the issue of language acquisition is interesting. Acquisition as an unconscious process is important when someone acquire a language. It contrasted with learning, which is a conscious process. The process of language acquisition and language learning influences by some factors. The process of language acquisition can be viewed from the perspectives of psycholinguistic, sociolinguistic, and neurolinguistic. From neurolinguistics perspective examines the nervous system in the human brain has an important role the process of acquiring a foreign language; includes external and internal factors of the human environment. This article discusses the process of Arabic language acquisition for non-native students.DOI: 10.15408/a.v2i1.1797